Comparative transcriptome analysis reveals immune-related genes involved in allograft and xenograft transplantation in Pinctada fucata - Zheng, Yusi; Wang, Pei; Guo, Ying; Bai, Lirong; Yu, Dahui; Zhao, Sen (Frontiers in Marine Science, 2024)
Background The marine pearl culture industry is a key industry in the Beibu Gulf of China that achieves large-scale pearl production by artificial nucleus insertion in pearls. High-quality pearls can produced by xenotransplantation, but allotransplantation or xenotransplantation can lead to various immune responses, resulting in nucleus rejection or even the recipient shell death and thereby causing significant losses in pearl production. Methods Few studies have investigated the immune defenses of oysters related to allografts and xenografts. In this study, transcriptomic comparisons of allograft and xenograft Pinctada fucata haemocytes were conducted to identify genes associated with immune responses. Results A total of 33.11 Gbp of clean reads were generated from five P. fucata haemocytes. De-novo assembly of quality-filtered reads generated a total of 26,526 unigenes, with 22,002 known genes and 4,524 predicted novel genes. In addition, 34,904 novel transcripts were detected, with 15,620 novel alternative splicing isoforms of known protein coding genes and 4,605 belonging to novel protein coding genes, with the remaining 14,679 comprising long non-coding RNA transcripts. Functional enrichment analysis of immune-related differentially expressed genes (DEGs) using the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases revealed 36–44 significantly enriched GO terms and 34 significantly enriched KEGG pathways. Ten DEGs were subjected to validation of expression levels using RT-q PCR analysis, revealing generally consistent values as the high-throughput sequencing data. Conclusion Oyster haemocytes were comprehensively evaluated in this study using transcriptomic comparisons and with a focus on immune-related functional genes and pathways. The results revealed numerous DEGs related to immune function that can serve as the basis for subsequent immune response analysis of allotransplantation and xenotransplantation.